Prohibition of riba’ and interest-based financial intermediation: Comparative analysis between the consensus of Islamic jurists and the contemporary polemicists - Megat Nor Hashim, Putri Ellynazura; Akbar, Mohamed Aslam (Faculty of Islamic Economics and Business, UIN Sunan Kalijaga Yogyakarta, 2021)
Interest has long been outlawed, as we all know, and most monotheist religions agree on this restriction. Some economists argue, however, that today's market-driven interest rates in a competitive financial market are not the same as usury and that interest-based financial intermediation has served a useful purpose in resource allocation as well as risk allocation, given the interpersonal differences in risk preferences that exist in any society. Hence, it is necessary to determine if Islamic economics distinguishes between usury and interest. This paper tries to fulfill this requirement by reviewing a critical evaluation of the literature on the topic of this article's attention, which explains the concept of financial intermediation and follows the concept of prohibition. The paper then examines how the debate over the interpretative riba’ has brought the issue of interest into modern Islamic banking, even though the consensus of Islamic jurists rejects the recommended alternative structure. The study finishes by defining the nature of capital in an Islamic economy and how it can be valued without compensating it with fixed payoffs, as well as assessing how economic and financial decisions will be affected in this new interest-free environment.